Brum, Eliane (2024). La Amazonia: Viaje al centro del mundo - Briana Bombana (Documents d'Anàlisi Geogràfica)
Brum, Eliane (2024) La Amazonia: Viaje al centro del mundo Barcelona: Miradas Salamandra, 432 p. ISBN 978-84-19456-39-7